Development of a Highly Selective Plasmodium falciparum Proteasome Inhibitor with Anti‐malaria Activity in Humanized Mice. (11th March 2021) - Zhan, Wenhu; Zhang, Hao; Ginn, John; Leung, Annie; Liu, Yi J.; Michino, Mayako; Toita, Akinori; Okamoto, Rei; Wong, Tzu‐Tshin; Imaeda, Toshihiro; Hara, Ryoma; Yukawa, Takafumi; et al.
Abstract: Plasmodium falciparum proteasome (Pf20S) inhibitors are active against Plasmodium at multiple stages—erythrocytic, gametocyte, liver, and gamete activation stages—indicating that selective Pf20S inhibitors possess the potential to be therapeutic, prophylactic, and transmission‐blocking antimalarials. Starting from a reported compound, we developed a noncovalent, macrocyclic peptide inhibitor of the malarial proteasome with high species selectivity and improved pharmacokinetic properties. The compound demonstrates specific, time‐dependent inhibition of the β5 subunit of the Pf20S, kills artemisinin‐sensitive and artemisinin‐resistant P. falciparum isolates in vitro and reduces parasitemia in humanized, P. falciparum ‐infected mice. Abstract : Pf20S inhibitors possess the potential to be therapeutic, prophylactic, and transmission‐blocking antimalarials. We present a novel and highly species‐selective malaria proteasome inhibitor that potently reduced parasitemia in humanized mice infected with P. falciparum, the deadliest plasmodium parasite.